2006
DOI: 10.1093/jac/dkl239
|View full text |Cite
|
Sign up to set email alerts
|

The influence of metallo- -lactamase production on mortality in nosocomial Pseudomonas aeruginosa infections

Abstract: MBL-PA infections resulted in higher mortality rates most likely related to the severity of these infections and less frequent early institution of appropriate antimicrobial therapy. Empirical treatments should be reviewed at institutions with high prevalence of MBL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
88
2
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(106 citation statements)
references
References 20 publications
8
88
2
8
Order By: Relevance
“…2 Pseudomonas aeruginosa is one of the most common causes of nosocomial infections, persisting at hospital environment and acquiring mobile elements of resistance. 3 The emergency of MBL in clinical isolates of P. aeruginosa is worrisome, due to the reduction of therapeutic options and the spreading ability of this bacterium. In addition, longer length of hospital stay and high mortality rates are associated to MBL producing P. aeruginosa infections.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…2 Pseudomonas aeruginosa is one of the most common causes of nosocomial infections, persisting at hospital environment and acquiring mobile elements of resistance. 3 The emergency of MBL in clinical isolates of P. aeruginosa is worrisome, due to the reduction of therapeutic options and the spreading ability of this bacterium. In addition, longer length of hospital stay and high mortality rates are associated to MBL producing P. aeruginosa infections.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, longer length of hospital stay and high mortality rates are associated to MBL producing P. aeruginosa infections. 3 Besides β-lactam resistance, P. aeruginosa susceptible only to colistin or polymyxin B has been described [3][4][5] in several infectious processes, which demand the increase use of these drugs. An accurate, easy-to-perform and fast phenotypic test to detect MBL is concentrations (MIC) ranging from 0.094 to 2; MIC 50 : 0.5; MIC 90 : 1.5 µg/mL; 100% susceptible].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In P. aeruginosa, a leading cause of nosocomial infections, MBLs pose serious therapeutic problems because treatment options are usually limited due to a combination of inherent resistance to many antimicrobial agents and its ability to develop resistance [3,4]. Recent studies have reported that MBL production caused a higher mortality rate because of the inappropriateness of early therapy [5,6], indicating a critical need for new agents effective against MBLproducing strains.…”
Section: Introductionmentioning
confidence: 99%